Molecular dynamic simulation reveals the inhibiting impact of Rhein on wild-type and P29S-mutated Rac1 - Etebar, Negar; Hamidi, Seyed Hootan; Naderpour, Saghi; Abouali, Omar; Hamidi, Seyedeh Harir; Hajipour-Verdom, Behnam; Rahimzadegan, Milad (Frontiers Media Sa, 2024)
Ras-related C3 botulinum toxin substrate 1 (Rac1) is a small GTPase belonging to the Rho family. It acts as a binary molecular switch regulating several cellular functions, including cell adhesion and migration. Malfunctions due to the P29S mutation in Rac1 increase the stability of the activated form of Rac1. This sustained activation can drive aberrant cellular processes associated with cancer, such as cell proliferation, survival, and migration. Therefore, finding an inhibitor that can inhibit the mutant form of the protein is very important. Rhein, a natural compound with diverse pharmacological properties, has been studied in relation to Rac1. However, specific interactions between Rhein and Rac1 have not been examined. In this study, we investigated the potential of Rhein, a natural compound, as an inhibitor of two forms of Rac1: the wild type and the P29S mutation, using molecular dynamics simulations. Results indicated that the P29S mutation led to structural changes in the Rac1 protein, which resulted in greater accessibility of the Rhein to the active site. In addition, the binding energy of Rhein to mutant Rac1 was more negative than the native protein. Therefore, it seems that the Rhein has a better inhibitory effect on the P29S-mutated form of the Rac1 protein.
Keywords: cancer; Rac1; Rhein; P29S mutation; molecular dynamics simulation